AN INVESTIGATION OF THE NOISE ABSORPTION POTENTIAL OF A SIX SELECTED GRASS SPECIES - N. D. AMARASINGHA; BODHIKA J. A. P.; DHARMARATNA W. G. D.; JAYATISSA L. P. (Journal of Applied Life Sciences and Environment)
Grass has a high leaf density and requires minimum space to grow. This experiment was designed to determine the sound absorption behaviour of six grass species (Zoysia matrella (L) Merr., Stenotaphrum dimidiatum(L.) Brongn, Panicum repens (L.), Eleusine indica (L.) Gaertn., Axonopus compressus (Sw) P. Beauv, and Ischaemum sp.) for their possible use as noise screens. The sound absorption of each morphological leaf structure was studied. For Sound Absorption Coefficients (SAC) (α) studies, the reverberation room method under ISO 345:2003 standards was followed. A B&K dodecahedron Omni-directional speaker, power amplifier, and 2250L handheld analyser were used for reverberation time and RT60 measurements. Microscopic images of grass leaves were analysed using ImageJ software. This study revealed that grasses with the highest and lowest SAC for higher noise frequencies (> 1500 Hz) are S. dimidiatum Brongn and A. compressus, respectively. The SAC of S. dimidiatum Brongn positively correlated with noise frequency. In general, the correlation of SAC (α) with noise frequency (f) is in the form of log10α = a1log10f + b1 where a1 and b1 are grass type-dependent constants. The morphological parameters like total leaf area, total sample area, plant height, and sample dry weight strongly correlated with the SAC. But leaf thickness, length, width, surface area, and the weight of the sample poorly correlated with SAC in the frequency range.